Working together to increase Australian children's liking of vegetables: a position statement by the Vegetable Intake Strategic Alliance (VISA) - David Nicholas Cox; Karen J Campbell; Lynne Cobiac; Claire Gardner; Lucinda Hancock; Gilly A Hendrie; Amber Kelaart; Michelle Lausen; Astrid AAM Poelman; Ros Sambell; Kim M Tikellis; Bonnie Wiggins (Cambridge University Press, 2023)
Children need to be repeatedly and consistently exposed to a variety of vegetables from an early age to achieve an increase in vegetable intake. A focus on enjoyment and learning to like eating vegetables at an early age is critical to forming favourable lifelong eating habits. Coordinated work is needed to ensure vegetables are available and promoted in a range of settings, using evidence-based initiatives, to create an environment that will support children's acceptance of vegetables. This will help to facilitate increased intake and ultimately realise the associated health benefits. The challenges and evidence base for a new approach are described.